Improved harvest and fixation methodology for isolated human peripheral blood mononuclear cells in cytokinesis-block micronucleus assay. (1st February 2021) - Goh, Valerie Swee Ting; Nakayama, Ryo; Blakely, William F.; Abe, Yu; Chua, Christelle En Lin; Chew, Zi Huai; Nakata, Akifumi; Fujishima, Yohei; Yoshida, Mitsuaki A.; Kasai, Kosuke; Ariyoshi, Kentaro; Miura, Tomisato
Abstract: Purpose: In suspected radiation exposures, cytokinesis-block micronucleus (CBMN) assay is used for biodosimetry by detecting micronuclei (MN) in binucleated (BN) cells in whole blood and isolated peripheral blood mononuclear cell (PBMC) cultures. Standardized harvest protocols for whole blood were published by the International Atomic Energy Agency (IAEA) in 2001 (Technical report no. 405) and 2011 (EPR-Biodosimetry). For isolated PBMC harvest, cytocentrifugation of fresh cells is recommended to preserve cytoplasmic boundaries for MN scoring. However, cytocentrifugation utilizes specialized equipment and long-term cell suspension storage is difficult. In this study, an alternative CBMN harvest protocol is proposed for laboratories interested in culturing PBMCs and storing fixed cells with routine biodosimetry methods. Materials and methods: Peripheral blood from 4 males (24, 34, 41, 51 y.o.) and females (26, 37, 44, 56 y.o.) was irradiated with 0 and 2 Gy X-rays. For cells harvested with IAEA 2001 and 2011 protocols, whole blood was used. For cells harvested with our protocol (CRG), isolated PBMCs were used. CRG protocol was validated in DAPI, acridine orange and Giemsa stain, and in three other laboratories. Cytoplasm status, nuclear division index (NDI) and induced MN frequency (MN frequency at 2 Gy – background MN frequency at 0 Gy) (MN/1000 BN) of Giemsa-stained BN cells were compared in IAEA 2001, IAEA 2011, IAEA 2011 + formaldehyde (FA) and CRG protocols. Effects of low and high humidity spreading were evaluated. Results: >94% of 1000 BN cells were scorable with clear cytoplasmic boundaries in all donors harvested with CRG protocol. FA addition in IAEA 2011 protocol reduced cell rupture in whole blood cultures, but cell rupture was affected by age, sex and humidity. Almost all cells harvested with IAEA 2001 protocol had cytoplasm loss. PBMCs harvested with CRG protocol stained well in DAPI, acridine orange and Giemsa, and showed high scorable BN frequency in all laboratories. A higher NDI and a lower induced MN frequency were seen in 2 Gy isolated PBMC than whole blood cultures. Conclusion: This quick CBMN harvest protocol for isolated PBMCs is a viable alternative to cytocentrifugation, as many scorable BN cells were obtained with routine biodosimetry reagents and equipment. IAEA 2011 + FA protocol should be used to improve CBMN harvest in whole blood cultures. Humidity during spreading should be optimized depending on the harvest protocol. NDI and MN frequency should be separately evaluated for whole blood and isolated PBMC cultures.